2012
DOI: 10.1111/j.1756-185x.2012.01734.x
|View full text |Cite|
|
Sign up to set email alerts
|

Adalimumab significantly reduces inflammation and serum DKK‐1 level but increases fatty deposition in lumbar spine in active ankylosing spondylitis

Abstract: Our study found that adalimumab was highly effective in reducing inflammation in active AS patients, but it was accompanied by the formation of FDL in the lumbar spine and decrease in serum DKK-1 levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…Using both randomisation method details and a baseline assessment to judge the risk of selection bias, 15 trials were judged as having a low risk of selection bias, five trials were judged as having an unclear risk 51,71,86,96,112 and four as having a high risk; 50,79,83,101 in one of these four trials the risk was deemed likely to be a result of a chance effect. 79 The risk of performance bias arising from lack of blinding of participants and personnel was low in 20 trials, unclear in three trials 55,57,64 and high in the one head-to-head trial, in which blinding would have been difficult to achieve because of the different modes and timings of delivery (weekly injection for etanercept vs. 6-weekly infusion for infliximab). 88 All except one of the trials were at low risk of detection bias, as they were all adequately placebo controlled (except the head-to-head trial), with nearly all the key outcomes being self-reported by patients (a notable exception being BASMI).…”
Section: Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations
“…Using both randomisation method details and a baseline assessment to judge the risk of selection bias, 15 trials were judged as having a low risk of selection bias, five trials were judged as having an unclear risk 51,71,86,96,112 and four as having a high risk; 50,79,83,101 in one of these four trials the risk was deemed likely to be a result of a chance effect. 79 The risk of performance bias arising from lack of blinding of participants and personnel was low in 20 trials, unclear in three trials 55,57,64 and high in the one head-to-head trial, in which blinding would have been difficult to achieve because of the different modes and timings of delivery (weekly injection for etanercept vs. 6-weekly infusion for infliximab). 88 All except one of the trials were at low risk of detection bias, as they were all adequately placebo controlled (except the head-to-head trial), with nearly all the key outcomes being self-reported by patients (a notable exception being BASMI).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In two of the trials with unclear risk judgements, there were nevertheless reasons to suspect the possibility of important bias (see Appendix 3). 55,71 Of the studies with missing data which also reported details on the populations and imputations used in analyses, 'last observation carried forward' (LOCF) was used; this was done using a modified intention-to-treat (mITT) approach in just over half the trials (in which patients had to have received at least one dose of treatment) and an intention-to-treat (ITT) approach in the remaining trials (see Appendix 3). There was no evidence of reporting bias in any of the trials with all being judged as low risk, except for one trial with an unclear risk of bias.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In theory, the activation of Wnt pathway would be facilitated by decreased expression of DKK-1, while the serum expression of DKK-1 in AS has been controversial. [7][8][9][10][11][12][13][14][15][16][17][18] To the best of our knowledge, other components of Wnt pathway have not yet been studied.…”
mentioning
confidence: 99%